Effects of temperature, relative humidity, and protective netting on Tyrophagus putrescentiae (schrank) (sarcoptiformes: Acaridae) infestation, fungal growth, and product quality of cave-aged Cheddar cheese. (September 2019) - Krishnan, Kavitha; Campbell, Yan L.; To, K. Virell; Lima, Gisele; Byron, Michael D.; Zhang, Xue; Hendrix, Jasmine D.; Shao, Wenjie; Cord, Christine L.; Crist, Courtney A.; Phillips, Thomas W.; Schilling, M. Wes
Abstract: Research was conducted to evaluate the effects of using food-grade ingredients on cave aged Cheddar cheese as either a surface coating or in nets to prevent infestation by T yrophagus putrescentiae growth at different environmental conditions. Food grade coating formulations with 1) xanthan gum and propylene glycol (XG+PG) and 2) carrageenan, propylene glycol alginate, and PG (CG+PGA+PG) were made and infused into nets. Jars with cave aged Cheddar cheese cubes that were inoculated with 20 mites were stored in an environmental chamber for 14 d at temperature and relative humidity (RH) combinations of 10, 15, and 20 °C and 75 ± 2 and 85 ± 2% RH. When averaged over RH, mite counts were fewer on control cheese cubes at 10 °C when compared to 15 °C and 20 °C, regardless of whether nets were used or not. However, mites were able to reproduce on untreated cheese cubes at all temperatures. The CG+PGA+PG and XG+PG coatings and nets controlled mite reproduction, as evidenced by harboring less than the initial inoculation level of 20 mites. Sensory results indicated that CG+PGA+PG and XG+PG coated Cheddar cheese at 10 °C and 75% RH and netted Cheddar cheese at 10 or 15 °C and 75% RH did not differ (P > 0.05) from the control with respect to sensory attributes. The treatments at 15 °C and 85% RH and 20 °C caused the cheese to be softer and more bitter than control cheese. In conclusion, the CG+PGA+ 40% PG and XG+40% PG treatments of both coatings and nets inhibited the growth of mites, and the use of nets lessened the impact of food grade coatings on the sensory properties of the Cheddar cheese. Highlights: Treated nets had fewer mites on Cheddar cheese cubes than the original inoculum level. Minimum mite growth occurred in untreated Cheddar cheese cubes at 10 °C. Treated nets were effective at controlling mite reproduction and mold growth.